Power generated by underwater strokes in front crawl swimming and its kinematic contributing factors - Kudo, S.; Yanai, T.; Matsuda, Y. (Journal of Biomechanics, 2025)
This study aimed to determine power generated by underwater strokes in front crawl swimming and discuss the kinematic contributing factors in upper-body segmental rotations to that power generated by underwater strokes. For 14 male swimmers performing front crawl swimming at maximal effort, the kinematics of the upper-body segments and hydrodynamic forces acting on the stroking hands were computed. Power generated by underwater strokes, its elements and components representing each segmental rotation were computed as the dot product of the force exerted on the water by the hands and hand velocity induced by the segmental rotations of the thorax, upper arm and forearm. Power generated by underwater strokes yielded two peaks in the pull (237 W) and push phases (221 W). The average power was strongly associated with swimming speed (r = 0.806). Contributions of the segmental rotations of the thorax, upper arm and forearm to power generated by underwater strokes were 32 %, 83 %, and -15 % in the pull phase, while 32 %, 37 %, and 31 % in the push phase, respectively. In the pull phase, the shoulder adduction contributed predominantly to the increase in power generated by underwater strokes, followed by the thoracic roll. In the push phase, the thoracic roll, the shoulder adduction and the elbow extension were equally important to increase that power. This study introduced power generated by underwater strokes as a crucial factor for assessing front crawl performance in the stroke phases and identified key segmental rotations that lead to the increased that power and, consequently, improved performance.